2002
DOI: 10.1007/s11746-002-0512-8
|View full text |Cite
|
Sign up to set email alerts
|

CLA formation in oils during hydrogenation process as affected by catalyst types, catalyst contents, hydrogen pressure, and oil species

Abstract: The effects of types and amount of catalysts, hydrogen pressure, and kinds of vegetable oils on the formation of CLA isomers were studied during hydrogenation. CLA isomers were identified by using a silver ion-impregnated high-performance liquid chromatograph and 100-m cyano-capillary column gas chromatograph. A selective catalyst (SP-7) produced a considerably higher content of CLA in soybean oil than nonselective catalysts. The maximal quantity of CLA produced in soybean oil during hydrogenation increased gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 23 publications
4
31
0
Order By: Relevance
“…The formation of these isomers was favoured at low hydrogen pressures (4 psi). Jung et al (2001Jung et al ( , 2002 reported the effect of hydrogen pressure on the quantity of CLAs in hydrogenated soybean oil using selective Ni catalysts. They demonstrated that when the hydrogen pressure increased, the total CLA content in soybean oil decreased.…”
Section: Hydrogen Pressure Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of these isomers was favoured at low hydrogen pressures (4 psi). Jung et al (2001Jung et al ( , 2002 reported the effect of hydrogen pressure on the quantity of CLAs in hydrogenated soybean oil using selective Ni catalysts. They demonstrated that when the hydrogen pressure increased, the total CLA content in soybean oil decreased.…”
Section: Hydrogen Pressure Effectmentioning
confidence: 99%
“…Several studies on CLA enrichment of vegetable oils, without the triglycerides hydrolysis, have been carried out in the past few years. Jung et al (2001Jung et al ( , 2002 reported the effects of catalyst type, catalyst amount, reaction temperature, agitation rate, hydrogen pressure and different oils on the quality and quantity of CLAs of hydrogenated soybean oil using a selective Ni catalyst. They concluded that the gas-liquid mass transfer limitation conditions at low hydrogen pressure, low stirring rate, high catalyst content and high reaction temperature favoured the CLA production in vegetable oils during hydrogenation and reached 250 mg g −1 oil.…”
Section: Introductionmentioning
confidence: 99%
“…Resulting hydrogenated soybean oil was subjected to Ag + -HPLC for isolation and identification of individual CLA isomers. Elution patterns of chromatographic peaks for authentic CLA methyl esters and soybean oil FAME standards were the same as reported previously (11,21,28). The individual Ag + -HPLC peak of hydrogenated soybean oil was identified based on comparison with authentic CLA standards (22,29).…”
Section: Resultsmentioning
confidence: 97%
“…Hydrogenation conditions were essentially the same as reported by Jung et al (11,21). Hydrogenation was carried out using the commercially available selective catalyst SP-7 (Engelhard) with an amount of 0.3% (w/w) catalyst, a hydrogen pressure of 0.24 MPa, a temperature at 230 o C, and an agitation rate at 300 rpm for 320, 360, and 380 min for soybean, cottonseed, and corn oils, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation